(untitled) (Bombay Hospital Journal, 2024)
Syncope is one of the common presenting symptoms in neurology clinics and emergency departments. Apart from the usual neurological and cardiovascular causes of syncope, there are a few rare triggers that cause transient loss of consciousness like coughing, swallowing, micturition, defecation, and laughing. These neurally mediated syncopes are labelled as “Situational” syncope. We report a case of a 28-year-old male who presented with episodes of dizziness, lightheadedness, and transient loss of consciousness mostly after excessive laughter. He has had similar episodes of transient loss of consciousness and lightheadedness after prolonged excessive laughing spells. This case is one of the very few described in medical literature, most of which have similar presentations and findings on subsequent investigations.